(untitled) (Journal of the Sylhet Agricultural University, 2025)
The goal of the study was to assess the productivity and growth of polyculture prawn and carps cultivation at various stocking ratios in Bagerhat district over a four-month period from April to July 2022. Three treatments based on stocking ratios and three repetitions were employed in the randomized block design (RBD) experiment. Fingerlings of major carps (Catla catla, Labeo rohita, and Cirrhinus mrigala) and prawn (Macrobrachium rosenbergii) post larvae in T1, T2, and T3 were provided in the following ratios such as 3:1:1:1, 4:1:1:1, and 5:1:1:1, respectively. Both prawns and carps received daily meals consisting of both commercially prepared feeds and formulated feeds made on the farm. Recorded water quality were found to be within acceptable levels for prawn production and to not exhibit significant variations (p<0.05) among the treatments. The highest growth of prawn was observed in T1 (42.00 g), surpassing T2 (40.00 g) and T3 (37.00 g). Prawn growth and survival rates were minor in T3, when there was a greater stocking ratio. While T2 exhibited higher prawn production (1168.00 kg ha-1) compared to T3 (1036.00 kg ha-1) and T1 (945.00 kg ha-1). As opposed to, the highest production was obtained in T1 (734.40 kg ha-1) and the lowermost in T3 (486.00 kg ha-1) for catla. In case of rui, the highest production was obtained in T1 (830.00 kg ha-1) and the lowermost in T3 (702.00 kg ha-1). The highest production was obtained in T1 (752.40 kg ha-1) and the lowest in T3 (702.00 kg ha-1) for mrigal. T2 produced significantly (p<0.05) more prawn and carps collectively (3303.80 kg ha-1) than T1 (3261.0 kg ha-1) and T3 (2926.0 kg ha-1), respectively. The net profit was found significantly higher in T2 (BDT 2,77,305.00 ha-1) where the ratio of prawn and carp species was 4:1:1:1/m2 followed by T3 (BDT 2,29,686.00 ha-1) with stocking ratio of 5:1:1:1/m2 and T1 (BDT 1,77,393.00 ha-1) with stocking ratio of 3:1:1:1/m2. As such, it is proposed that prawn farmers employ the stocking ratio that’s 4:1:1:1/m² for the concurrent production of prawns and big carps aiming to enhance both prawn and fish production and economic profitability. J. Sylhet Agril. Univ. 11(1): 09-16, 2024